Diversity Of Chiropterans In Limestone Forest Area, Bau, Sarawak - Mohd-Azlan, J.; J., Neuchlos; M.T, Abdullah (Malaysian Applied Biology Journal, 2005)
A study on understory chiropteran diversity and relative abundance was examined using harp traps and mist nets around Bau Limestone area, Sarawak. A total of 23 species from four families were captured during 20 sampling nights. This represents approximately 24% of the total species recorded in Borneo. A total of 107 and 43 individuals of bats were captured using harp traps and mist nets respectively. The most frequently captured species was Penthetor lucasi followed by Hipposiderous galeritus, which comprised 25% and 14% of the total capture respectively. Even though the species accumulation curve showed signs of levelling out, additional effort at the sub-canopy and canopy level may yield in higher diversity record.